Organic acids as potential growth promoters in abalone culture - Goosen, Neill Jurgens (Stellenbosch : Stellenbosch University, 2011)
ENGLISH ABSTRACT: The first successful captive spawning of the South African abalone Haliotis midae occurred in the 1980’s and subsequently the commercial abalone industry in South Africa has developed, with an estimated investment of US$ 12 million and annual output of 500 to 800 tons by 2001, making South Africa the biggest abalone producer outside of Asia. Natural kelp is currently the major feed and the development of a suitable substitute, and improved disease management in abalone culture are seen as the primary factors limiting expansion of the industry in South Africa. Further, abalone growth rates are very slow and improvements in growth rate will lead to shortened production times with benefits to producers. Diseases in aquaculture have traditionally been combated using antibiotics as treatment (therapeutic usage) and preventative measure (prophylactic usage). In terrestrial livestock management, antibiotics are also used as growth promoters. The use of antibiotics in aquaculture has recently sparked concerns about the development of antibiotic resistance in pathogens of humans and aquaculture organisms, and alternative strategies to using antibiotics mainly focus on manipulating the microbial composition in the host organism, in order to establish a beneficial microbial population to prevent disease. The role that organic acids and their salts can play as growth promoters in the South African abalone Haliotis midae, and as manipulators of the gut microflora of this species of abalone was investigated and compared to the effects of antibiotics. Three different treatments were tested against a negative control and a positive control containing 30ppm avilamycin, a commercial antibiotic growth promoter (AGP) used in the pig and poultry industry. The 3 treatments consisted of 1% acetic and 1% formic acid (treatment AF), 1% sodium benzoate and 1% potassium sorbate (treatment SBPS), and 1% benzoic and 1% sorbic acid (treatment BS). Three different experiments were conducted to test the effects of the different acids and salts. The first experiment was under controlled optimum water temperature conditions (16.5ºC), another at elevated water temperature (20.5ºC) in order to test response during temperature stress conditions, and the final trial was conducted under uncontrolled practical production conditions. In an attempt to establish the mechanism by which the treatments have their effects (if any), the composition of the gut microflora of the abalone was monitored. It was found that the organic acids and salts investigated can enhance the growth rate of Haliotis midae in the size class 23 mm to 33 mm mean length significantly when compared to both control treatments. It was further found that the tested AGP had no effect on growth rate. None of the treatments had a significant effect on feed conversion ratio (FCR), Incidence cost (IC) or feed intake. It could also not be shown that the treatments affected the intestinal microflora of the abalone, although this might be due to inadequate microbiological methods. The mechanism by which the acids and salts have their effects could not be established. It was found that the animals in the controlled system underwent an initial adaptation period, which led to improvement in specific growth rate (SGR), FCR and IC as the experiment progressed during the controlled optimal conditions experiment. Large differences in FCR and IC was seen for controlled optimal conditions and production conditions which means that there is still a large scope for developing methods to improve practical on-farm feed utilisation by abalone. SGR, FCR and IC were negatively influenced by raising water temperature from 16.5ºC to 20.5ºC. The composition of the gut microflora of the abalone also changed significantly after the water temperature was raised. It appears that animal weight gain and shell growth respond differently to changing water temperatures, which is reflected in a change in Fulton condition factor. A relationship between the length and weight of abalone between 15 mm and 47 mm was established and it was found that Haliotis midae does not follow an isometric growth relationship. This relation can be used as a tool to improve farm management and therefore also profitability. Various micro-organisms were isolated from Haliotis midae during the trial, but their relationship and interaction with abalone is not clear. Clear dominance by specific species of bacteria was observed during certain periods. The current research has clearly showed the potential of organic acids and their salts to act as growth promoters in the South African abalone Haliotis midae, with application in both the local aquaculture and feed manufacturing industries. The possibility further exists that some aspects of the current research can be adapted to be applicable in other abalone species and even in other aquaculture species.